2017
DOI: 10.1016/j.chom.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A Rab20-Dependent Membrane Trafficking Pathway Controls M. tuberculosis Replication by Regulating Phagosome Spaciousness and Integrity

Abstract: SummaryThe intracellular pathogen Mycobacterium tuberculosis (Mtb) lives within phagosomes and also disrupts these organelles to access the cytosol. The host pathways and mechanisms that contribute to maintaining Mtb phagosome integrity have not been investigated. Here, we examined the spatiotemporal dynamics of Mtb-containing phagosomes and identified an interferon-gamma-stimulated and Rab20-dependent membrane trafficking pathway in macrophages that maintains Mtb in spacious proteolytic phagolysosomes. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 47 publications
(75 reference statements)
3
89
0
Order By: Relevance
“…In contrast, macrophages harbouring the LRRK2 gain‐of‐function mutation G2019S were more susceptible to Mtb replication (Fig M) and showed a reduction in lysosomal targeting of Mtb to phagolysosomes as measured by LAMP‐1 recruitment (Fig N and O). An image‐based approach (Schnettger et al , ) confirmed reduced Mtb growth in LRRK2 KO macrophages and enhanced growth in G2019S KI macrophages (Fig EV1G and H). Moreover, IFN‐γ activation and control of Mtb was not synergistic (Fig EV1I) and enhanced Mtb phagosome maturation was not due to a general defect in late endosomal morphology (LAMP‐1) or CtsL activity (Fig EV2).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast, macrophages harbouring the LRRK2 gain‐of‐function mutation G2019S were more susceptible to Mtb replication (Fig M) and showed a reduction in lysosomal targeting of Mtb to phagolysosomes as measured by LAMP‐1 recruitment (Fig N and O). An image‐based approach (Schnettger et al , ) confirmed reduced Mtb growth in LRRK2 KO macrophages and enhanced growth in G2019S KI macrophages (Fig EV1G and H). Moreover, IFN‐γ activation and control of Mtb was not synergistic (Fig EV1I) and enhanced Mtb phagosome maturation was not due to a general defect in late endosomal morphology (LAMP‐1) or CtsL activity (Fig EV2).…”
Section: Resultsmentioning
confidence: 85%
“…As observed with latex beads (Fig EV5), Rubicon was recruited during the first 15 min after phagocytosis (Fig G). In Rubicon KD mouse macrophages (Fig H), the percentage of LAMP‐1‐positive Mtb phagosomes (Fig I and J) and Mtb phagosome showing pan‐cathepsin activity (Schnettger et al , ; Fig K and L) was significantly higher after Rubicon KD when compared to the scrambled control. As expected, LRRK2 kinase inhibition did not further enhance LAMP‐1 recruitment (Fig I and J) or pan‐cathepsin activity (Fig K and L) of Mtb phagosomes from Rubicon‐depleted macrophages.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, membrane damage still occurred in the absence of LRRK2 signalling, suggesting that LRRK2 specifically affects membrane damage recognised by Galectin‐3. We next used the lysosomotropic dye LysoTracker to monitor lysosomal integrity dynamics (Schnettger et al , ; Radulovic et al , ). Damaged endolysosomes in LRRK2 or Rab8A KO macrophages leaked LysoTracker faster and to a higher extent when compared to WT macrophages (Fig C and D).…”
Section: Resultsmentioning
confidence: 99%
“…To protect themselves from the potential detrimental consequences, mammalian cells have several mechanisms to recognise and restrict the damage of endomembranes. The ESCRT‐III machinery repairs membranes that show limited damage (Radulovic et al , ; Skowyra et al , ) whereas it has been proposed that endosomes or autophagosomes repair membranes that have been extensively damaged by intracellular pathogens (Kreibich et al , ; Schnettger et al , ; Lopez‐Jimenez et al , ). Alternatively, damaged endolysosomes are targeted to lysophagy (autophagy of lysosomes) for degradation (Settembre et al , ; Maejima et al , ).…”
Section: Introductionmentioning
confidence: 99%